Plastic instability in complex strain paths and finite element simulation for localised necking prediction in sheet metal forming technology - A. Barata da Rocha (2008)
Formability of sheet metals is a measure of its ability to deform plastically, being mainly limited by the occurrence of flow localisation or instability. Plastic instability numerical models have been used to predict such behaviour and recent and more accurate constitutive plasticity models have been applied in these calculations. Combination of Forming Limit Diagram (FLD) analysis with Finite Element (FE) simulations often fail to give the right answer, if complex strain paths are not included. This paper presents a Plastic Instability Model developed to predict localised necking under complex strain paths, which may be used as FLD prediction code or as a FE post-processing tool for necking prediction. It is shown that considering the non-Linear Strain Paths in the analysis, more accurate failure predictions are achieved. An experimental component with necking occurrence is studied. The numerical simulation of this component by FEM is performed and necking is predicted by developed code.